Sabellaria isumiensis n. sp. (Annelida: Polychaeta: Sabellariidae) from shallow waters off Onjuku, Boso Peninsula, Japan, and re-descriptions of three Indo-West Pacific sabellariid species - Nishi, Eijiroh; Bailey-Brock, Julie Helen; Santos, Andre Souza Dos; Tachikawa, Hiroyuki; Kupriyanova, Elena K. (Zootaxa, 2010)
A new species of the genus Sabellaria Lamarck, 1812, is described from shallow waters off Onjuku, the Pacific side of Boso Peninsula, Chiba, Japan. Sabellaria isumiensis n. sp. is a gregarious species building colonies of tubes made of sand and shell debris over 2 m wide in the intertidal to subtidal zone of the rocky shores. The new species is distinguished by the character combination of having 1 or 2 pairs of nuchal spines, median teeth of outer paleae with 3–5 lateral spines, two kinds (long and short) of opercular paleae in the middle row of the crown, with slender blades of long ones curved outward. Morphological features of the species are described in details and compared to those of congeners from Japan and world-wide. We re-describe three poorly known sabellariid species, Sabellaria javanica Augener, 1934 from Java, Indonesia, S. chandraae de Silva, 1961 from Galle Force, Sri Lanka, and Neosabellaria uschakovi Kirtley, 1994 from the Far Eastern Seas of Russia. The descriptions are based on the type specimens, and we particularly emphasize the head morphology and paleal characters. We provide a summary of diagnostic characters in the genus Sabellaria and propose new morphological groupings that later will be tested in the framework of a formal phylogenetic analysis.